2009
DOI: 10.1007/s10499-009-9276-0
|View full text |Cite
|
Sign up to set email alerts
|

Rice fields to prawn farms: a blue revolution in southwest Bangladesh?

Abstract: This paper examines freshwater prawn (Macrobrachium rosenbergii) farming in southwest Bangladesh where a large number of farmers have converted their rice fields to export oriented prawn farms, locally known as gher. The gher design potentially provides good opportunities for diversified production of prawn, fish, rice and dike crops, that has brought about a 'blue revolution'. The average annual yield of prawn, fish and rice was estimated at 467, 986 and 2,257 kg ha -1 , respectively. Large farmers produced h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
91
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 91 publications
(93 citation statements)
references
References 18 publications
0
91
2
Order By: Relevance
“…Rising groundwater levels may additionally result from local recharge as the volume of rainfall-fed recharge exceeds abstraction for irrigation in southern deltaic areas (BGS and DPHE, 2001). Abstraction for irrigation has declined in coastal areas of Bangladesh where rapid growth in brackish-water shrimp farming since the early 1990s has replaced many low-lying rice fields (Ahmed et al, 2009). Projected rises in sea level will accelerate the intrusion of saline water thereby impairing groundwater quality and threatening the world's largest mangrove forest in the Sundarbans (Alam, 2004) where groundwater plays a vital role in maintaining an intermediate salinity required for mangrove growth and survival (Agrawala et al, 2003).…”
Section: Rising Groundwater Levels and Sea-level Risementioning
confidence: 99%
“…Rising groundwater levels may additionally result from local recharge as the volume of rainfall-fed recharge exceeds abstraction for irrigation in southern deltaic areas (BGS and DPHE, 2001). Abstraction for irrigation has declined in coastal areas of Bangladesh where rapid growth in brackish-water shrimp farming since the early 1990s has replaced many low-lying rice fields (Ahmed et al, 2009). Projected rises in sea level will accelerate the intrusion of saline water thereby impairing groundwater quality and threatening the world's largest mangrove forest in the Sundarbans (Alam, 2004) where groundwater plays a vital role in maintaining an intermediate salinity required for mangrove growth and survival (Agrawala et al, 2003).…”
Section: Rising Groundwater Levels and Sea-level Risementioning
confidence: 99%
“…Moreover, it made possible to involve the female members of the family in gher farming. Ahmed et al (2010) stated that women are also involved in feeding of prawns, dyke cropping, farm supervision, prawn harvesting and post harvesting handling. In the present study it was found that all the farmers indicated that they were able to improve their socio-economic status after being involved in the gher farming.…”
Section: Discussionmentioning
confidence: 99%
“…This study applied both quantitative and qualitative data collection methods which are used by the following authors, e.g., Ahmed et al [33]. Research was done in collaboration (to help identifying the respondents) with WAB Trading International.…”
Section: Methodsmentioning
confidence: 99%